My southern kitchen : from suppers to celebrations, recipes for every occasion - Odom, Ivy (Abrams : Southern Living, 2025)
"Southern Living magazine's beloved columnist and test kitchen pro Ivy Odom offers a host of truly Southern recipes, from favorites to fresh creations. Whether you already love her Southern Living cooking column and Hey Y'all video series or have just discovered them, you need to know Ivy Odom. Born and raised in Moultrie, Georgia, and just 30 years old, she is a fresh cooking talent whose star is ascendant. Her first cookbook mixes up tried and true classic recipes passed down through generations--Ivy's heritage is proudly Southern all the way--with her own trendworthy spins on traditional favorites. Throughout the book, you'll find big cooking ideas (plus time saving tips); cocktails to shake; and recipes (more than 100) to make to help you cook up all the dishes you crave. Chapters match food to occasion, so have fun indulging in your favorite supper menus, cocktails for porch sipping, and perfect dishes for lawn parties, lazy Sundays, tailgates, and more. Discover pro cooking techniques in "Ivy's Take" sidebars, and for moments when you'd rather read than cook, there are stories full of signature Southern charm on each and every page."--